Remittance and Tourism Income: Pillars of the National Economy of Nepal - Thapa, Khagendra Kumar; Regmi, Dipika; Dahal, Arjun Kumar (Adhyayan Journal, 2026)
This study aims to examine the role of tourism income in GDP growth, analyze the contribution of remittances to Nepal’s economic growth, and recommend strategies to maximize the benefits of tourism income and remittances. It is based on secondary data collected from the World Bank, Nepal Rastra Bank (NRB), the Ministry of Culture, Tourism and Civil Aviation (MoCTCA), and the International Monetary Fund (IMF) for economic data, and from research papers and journals for meaningful insights. It covers 20 data points from 2005 to 2024. This study is based on both an analytical and descriptive research design. It is guided by positivist research philosophy and deductive reasoning. Simple statistical tools, such as descriptive statistics, correlation, Johnson co-integration test, Ordinary Least Squares, and diagnostic tests for serial correlation, heteroskedasticity, and CUSUM and CUSUM square, are applied. Results show that one percent increase in remittances leads to a 0.816 percent increase in economic growth, whereas one percent increase in tourism income leads to a 0.1307 percent decrease in economic growth in Nepal. The value of R-squared is 0.9692. So, 96.92 percent of the variation in Nepal’s economic growth is explained by tourism income and remittances. John Co-integration tests consistently show that GDP, remittance, and tourism income share a stable long-run relationship, despite short-term fluctuations. The findings imply that Nepal should prioritize policies that strengthen and channel remittance inflows toward productive investment, while reforming and diversifying the tourism industry to ensure its long-run contribution to sustainable economic growth.